Legal Governance of Traditional Health Practitioners in Plural Legal Systems: Indonesia and China - Suhartono, Mutia Aprilia; Suhartono, Rizki Mustika; Salam, Safrin; Ribeiro, Leonito (SASI, 2026)
Introduction: This article examines the legal governance of traditional health practitioners within plural legal systems in Indonesia and China. Although traditional health practices function as living law rooted in customary knowledge, state regulation increasingly subjects them to licensing, standardization, and administrative control. This condition raises legal tension between customary norms and formal health law, particularly regarding professional recognition, legal authority, and protection of traditional knowledge within modern healthcare systems. Purposes of the Research: The purpose of this study is to analyze and compare how Indonesia and China regulate traditional health practitioners within plural legal systems, focusing on licensing mechanisms, state recognition, and the position of traditional knowledge as living law under contemporary health governance. Methods of the Research: This research employs normative legal research using a comparative law approach. The study applies statute and conceptual approaches to examine laws, regulations, and policy frameworks governing traditional health practitioners in Indonesia and China. Legal materials are analyzed qualitatively to identify governance models and normative gaps. Results of the Research: The findings show that both Indonesia and China formally recognize traditional health practitioners but regulate them through state-centric licensing systems that marginalize customary governance. China integrates traditional practitioners into its national health system, while Indonesia maintains fragmented regulation with limited customary recognition. This study contributes novel insights by positioning traditional health practice as living law and proposing the need for sui generis governance models that reconcile legal pluralism with regulatory certainty.